Rise in 2017-2018 measles morbidity in Serbia and Northwest Russia - V. D. Stoiljkovic (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
In 2017, the WHO registered 23,927 measles cases in 44 out of 53 countries in the European region. In 2018, measles incidence rate increased up to 82,599 cases registered in 48 countries of the region, with a large number of measles-associated deaths. Overall, 72 measles fatalities were registered in 10 European countries, including Serbia (15 cases).Aim of the study: to characterize 2017—2018 epidemiological upsurge of measles incidence rate observed in the Republic of Serbia (RS) and the Northwestern Federal District (NWFD) of the Russian Federation.Materials and methods. During the 2017—2018 season, 944 serum samples were collected from patients with measles, rubella, or exanthematous diseases in the NWFD and tested in the Laboratory of Virology at the St. Petersburg Regional Centre for Measles Surveillance (SPbRC). In 2017—2018, 2,946 serum samples from the Republic of Serbia were analyzed in the SPbRC by using ELISA with IgM measles test system (Vector-Best, Russia; or Siemens, Germany). Urine and swab samples were examined by RT-PCR and used for isolation and genotyping of measles viruses.Results. From 2017 to 2018, 5,798 measles cases were registered in the RS, among which 2,946 were laboratory-confirmed (serological testing and/or PCR). Unvaccinated subjects or those with unknown vaccination status accounted for majority of the cases. Children under 5 years of age and adults aged 30 years and over dominated among measles patients. During this season, 15 deaths were reported. Several genotypes of measles virus circulated in the RS, e.g. В3 Dublin, D8 Gir Somnath, and D8 Herborn. In 2018, 109 measles cases were recorded in the NWFD, 5 of which were imported from abroad. Among patients, adults comprised 64.2%, wherein 74.3% were covered by unvaccinated subjects or those with unknown vaccination status. Rise in measles incidence rate linked to multiple importations of various measles virus genotypes: В3 Kabul; B3 Dublin; D8 Frankfurt; D8 Cambridge; and D8 Gir Somnath.